2021
DOI: 10.1155/2021/2951697
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of the Potential Chemoprotective Effects of Resveratrol on Doxorubicin‐Induced Cardiotoxicity: Focus on the Antioxidant, Antiapoptotic, and Anti‐Inflammatory Activities

Abstract: Purpose. Although doxorubicin chemotherapeutic drug is commonly used to treat various solid and hematological tumors, its clinical use is restricted because of its adverse effects on the normal cells/tissues, especially cardiotoxicity. The use of resveratrol may mitigate the doxorubicin-induced cardiotoxic effects. For this aim, we systematically reviewed the potential chemoprotective effects of resveratrol against the doxorubicin-induced cardiotoxicity. Methods. In the current study, a systematic search was p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(9 citation statements)
references
References 150 publications
(257 reference statements)
0
9
0
Order By: Relevance
“…Isorhapontigenin, a new derivative of stilbene, alleviated CMA and cardiac atrophy caused by DOX, which is associated with the upregulation of yes-associated protein 1 expression (31). Resveratrol (3,5,4 ′ -trihydroxy-trans-stilbene, RES), a natural polyphenol which can be found mainly in grapes, red wine, soy, and peanuts, has been well studied in DIC protection (152). Earlier, Zhang et al found that RES prevented DOXinduced HW, BW, HW/BW ratio reduction, and cardiotoxicity via sirtuin 1(SIRT1)-p53 pathway (153).…”
Section: Polyphenolic Compoundsmentioning
confidence: 99%
“…Isorhapontigenin, a new derivative of stilbene, alleviated CMA and cardiac atrophy caused by DOX, which is associated with the upregulation of yes-associated protein 1 expression (31). Resveratrol (3,5,4 ′ -trihydroxy-trans-stilbene, RES), a natural polyphenol which can be found mainly in grapes, red wine, soy, and peanuts, has been well studied in DIC protection (152). Earlier, Zhang et al found that RES prevented DOXinduced HW, BW, HW/BW ratio reduction, and cardiotoxicity via sirtuin 1(SIRT1)-p53 pathway (153).…”
Section: Polyphenolic Compoundsmentioning
confidence: 99%
“…Several studies found that different dosages of LC, such as 150 and 300 mg/kg BW/day, had a protective impact on cardiomyocytes. Cardiotoxicity pathogenic alterations such necrotic muscle fibers and large inflammatory cellular infiltrations were reduced by LC [ 14 , 15 ]. LC + TRZ ( l -carnitine and TRZ) co-treated group Rats received TRZ (20 mg/kg/day) along with l -carnitine (200 mg/kg/day) for 28 days via oral gavage.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies found that different dosages of LC, such as 150 and 300 mg/kg BW/day, had a protective impact on cardiomyocytes. Cardiotoxicity pathogenic alterations such necrotic muscle fibers and large inflammatory cellular infiltrations were reduced by LC [14,15].…”
Section: Lc (Lcarnitine) Groupmentioning
confidence: 99%
“…Previous studies showed that ROS generated by DOX caused cardiac injury and cardiomyocyte apoptosis. 42,43 We detected ROS levels in H9C2 cells by DCFH-DA staining to further investigate the effect of Fc-Ma-DOX treatment on DOX-induced cardiotoxicity in vitro. The H9C2 cells were plated in 6-well culture plates at a density of 6 × 104 cells per mL and then treated with free DOX (5 mg mL −1 ), Fc-Ma (5 mg mL −1 ) and Fc-Ma-DOX (at a DOX equivalent dose of 5 mg mL −1 ) for 24 hours, as shown in Fig.…”
Section: Fc-ma-dox Inhibits Oxidative Stress and Apoptosis In Vitromentioning
confidence: 99%